Supplemental Material, Humpback-ABM-master - Using agent-based models to understand the role of individuals in the song evolution of humpback whales ( Megaptera novaeangliae ) ... - Mcloughlin, Michael; Lamoni, Luca; Garland, Ellen C.; Ingram, Simon; Kirke, Alexis; Noad, Michael J.; Rendell, Luke; Miranda, Eduardo (SAGE Journals, 2018)
Supplemental material, Humpback-ABM-master for Using agent-based models to understand the role of individuals in the song evolution of humpback whales ( Megaptera novaeangliae ) by Michael Mcloughlin, Luca Lamoni, Ellen C. Garland, Simon Ingram, Alexis Kirke, Michael J. Noad, Luke Rendell and Eduardo Miranda in Music & Science ...